Relationship between carotid intima-media thickness, physical activity, sleep quality, metabolic/inflamatory profile, body fatness, smoking and alcohol consumption in young adults - Santiago Maillane-Vanegas; Bruna Camilo Turi-Lynch; Fabio Santos de Lira; Jamile Sanches Codogno; Rômulo Araújo Fernandes; Manoel Carlos Spiguel de Lima; Aristides Machado-Rodrigues; Han C. G. Kemper (Universidade Estadual Paulista (UNESP), 2017)
Abstract AIM The aim of this longitudinal study was to analyze the relationship between sleep disorder and intima-media thickness. METHOD Baseline measurements included carotid intima-media thickness, assessed by an ultrasound device; questionnaires about sleep and other behavioral variables; physical activity was measured by pedometer; body fatness was estimated by Dual-Energy X-ray Absorptiometry; fasting glucose, lipid profile and C-reactive protein were collected. RESULTS The occurrence rate of sleep-related disorders was 47% (95%CI= 37.2%-56.7%). Carotid intima-media thickness was related to symptoms of insomnia (r= 0.328 [0.141 to 0.493]) and, after adjustments for potential confounders, the relationship between carotid intima-media thickness and insomnia remained statistically significant (β= 0.121 [95%CI= 0.017; 0.225]). CONCLUSIONS In young adults, sleep disorder was significantly related to premature increase in carotid intima-media thickness.